Importance of a prenatal care performed by a multidisciplinary team (Research, Society and Development, 2024)
Introduction: Prenatal care aims to welcome pregnant women by providing comprehensive monitoring through a set of activities that aim to prevent, diagnose and treat adverse pregnancy events. Therefore, this assistance helps at all stages of pregnancy, with the Basic Health Unit (UBS) being the preferred gateway for pregnant women to the health system and the multidisciplinary team being an important strategy for pregnancy monitoring. Objective: To report the experience of medical students, with an emphasis on the importance of prenatal care provided by a multidisciplinary team. Methodology: Descriptive study, experience report type, carried out in a Family Health Unit from the metropolitan Region of Cabedelo-PB. Results: Prenatal care is the recommended care for all pregnant women and multidisciplinary care proved to be necessary to provide safe and competent monitoring of pregnant women treated at the Basic Health Unit, as it encompasses several areas of knowledge essential for assistance. effective and resolute. Furthermore, this strategy makes it possible for all health professionals to commit to ensuring the care and well-being of the pregnant woman, her partner and the baby, reducing maternal and perinatal morbidity and mortality. Conclusion: It is concluded that prenatal care carried out by a multidisciplinary team, through the knowledge of different professionals, becomes essential for a more qualified prenatal care, bringing security to the pregnant woman, in pregnancy monitoring, delivery and care to the newborn.